Analisis Daya Saing Crude Palm Oil (CPO) Indonesia Di Pasar Internasional` - Sopia Azida; Muhammad Yamin; Riswani Riswani (AGRICA, 2023)
This study aims to evaluate Indonesia's competitiveness and assess the dynamics of Indonesia's CPO performance in the international market. Comparative CPO in Indonesia is carried out using the "Revealed Comparative Advantage" (RCA) technique, while the "Constant Market Share" (CMS) method is used to understand the dynamics of Indonesia's export performance. The results showed that Indonesia's CPO has a relative competitive advantage index (RCA) value of 4, indicating that Indonesia has a strong competitive advantage and an RCA greater than 1. According to CMS data, Indonesian CPO is not limited to one country's market and has a higher standard growth rate than the world's CPO exports, also has a positive impact on market distribution and product composition.